SPORTS ORIENTATION DURING LEARNING TEAM OR INDIVIDUAL SPORTS USING A SPORT EDUCATION MODEL - Agi Ginanjar; Adang Suherman; Tite Juliantine; Yusuf Hidayat (Jurnal Cakrawala Pendidikan, 2019)
Since competition activities can improve sportsmanship, moral development, motivation, and prepare students in the "real world", competition activities (sports orientation) in physical education is very necessary. A strategy that is proposed to stimulate sports orientation in physical education in this study is a Sport Education Model (SEM). The purpose of this study was to determine the differences between team sports and individual sports when using SEM, towards sports orientation in physical education for junior high school students. The research method uses true experiments with posttest-only control group design. The participants in this study were 80 grade seventh junior high school students. Using the Sport Orientation Questionnaire (SOQ), the data was analysed using independent samples t-test. The results stated that there were significant differences between the two conditions. The findings suggests that sports orientation in SEM team sports are more influenced by goal orientation is in accord with the statement that achievement in sports competition (sports orientation) depends on goal orientation, but not at SEM individual sports.